Bone mineral density in patients with idiopathic pulmonary fibrosis. Issue 9 (September 2015) - Ikezoe, Kohei; Handa, Tomohiro; Tanizawa, Kiminobu; Kubo, Takeshi; Oguma, Tsuyoshi; Hamada, Satoshi; Watanabe, Kizuku; Aihara, Kensaku; Sokai, Akihiko; Nakatsuka, Yoshinari; Muro, Shigeo; Nagai, Sonoko; et al.
Abstract: Background: Decreased bone mineral density (BMD) has been reported in patients with interstitial lung disease. However, BMD has not been evaluated in steroid-naïve patients with idiopathic pulmonary fibrosis (IPF). We aimed to measure vertebral BMD and investigate its relationship with clinical features in steroid-naïve patients with IPF. Methods: We recruited 55 consecutive male patients with steroid-naïve IPF; 55 male smokers without chronic obstructive pulmonary disease or interstitial lung disease, matched by age, body mass index, and pack-years of smoking (control smokers); and 27 healthy young adults. Thoracic vertebral BMD was measured by computed tomography (CT). We further investigated the relationship of BMD with clinical features and quantitative CT indices of lung density in patients with IPF. Results: The thoracic vertebral BMD of patients with IPF was significantly lower than that of control smokers (139.9 ± 28.5 mg/mL vs 160.9 ± 39.5 mg/mL, p < 0.01). Fifteen patients (27.2%) had BMD more than 2.5 SD below the mean BMD of young adults. In patients with IPF, emphysema volume (EV) and its ratio to total lung volume (EV%) had a significantly negative correlation with BMD (r = −0.28, p = 0.04 and r = −0.39, p < 0.01, respectively). In stepwise multiple regression analysis, EV% was an independent explanatory variable for thoracic vertebral BMD. Conclusion: A substantial percentage of steroid-naïve IPF patients had decreased BMD, and a significant association was observed between the extent of emphysema and BMD in IPF. Highlights: BMD is decreased in a substantial percentage of steroid-naïve IPF patients. The extent of emphysema correlates with BMD in patients with IPF. Chest CT may be useful to assess BMD and its associated clinical factors in IPF. Further studies are needed to clarify the precise mechanism of BMD decrease in IPF.